A Novel Stability-Indicating Method for Simultaneous Estimation of Glycopyrronium Bromide and Neostigmine Methyl Sulfate Injectable Formulations by RP-HPLC - Mashru, Chetankumar; Dhalani, Jayesh (Universitas Gadjah Mada, 2026)
Glycopyrronium bromide and neostigmine methyl sulfate drugs combination is used in treatment as an injectable formulation. The present study proposes the development and validation of an accurate, selective, and sensitive RP-HPLC method, which will enable the detection of degradation products for the combined estimation of glycopyrronium bromide and neostigmine methyl sulfate in both the parental dosage form and bulk samples. The optimum chromatographic condition was achieved using an octadecylsilane column, such as the Inertsil ODS-3 column with dimensions of 150 × 4.6 µm, 3 µm, at a flow rate of 1.00 mL/min with gradient elution. Phosphate buffer (pH 2.50) and acetonitrile were used as solutions A and B, respectively. Chromatography was achieved with an injection volume of 10 µL and a detection wavelength of 220 nm. The proposed study found a linear relationship between the ranges of 25–75 and 125–375 ppm for glycopyrronium and neostigmine methyl sulfate, respectively. The limit of detection and limit of quantification were achieved at 0.15 and 0.5 ppm for glycopyrronium bromide and neostigmine methyl sulfate, respectively. The validation of the method was carried out with a short run time of 20 min and a recovery rate of more than 99%.